Legal Optimization Through Juridical Study of Illegal Logging Crimes: Efforts to Prevent Adverse Environmental Damage - St Aisyah; Muh. Fadli Faisal Rasyid; Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2024)
This research aims to determine the consequences of illegal logging laws that result in environmental damage in the Enrekang Regency and identify the obstacles officers face in handling illegal logging cases that result in ecological damage in the Enrekang Regency. The type of research used is normative and empirical research. This research is supported by a Legislative Approach (statue approach) and a Social Approach (Social Approach). Illegal logging in Enrekang Regency is regulated in Law Number 18 of 2013, namely a maximum prison sentence of 5 years and a maximum fine of IDR 2.5 billion. Handling cases of illegal logging in Enrekang Regency faces several obstacles, namely, limited human resources for forestry police, difficulty in patrolling the forest, the size of the forest area, lack of budget, and lack of patrol vehicles